‘Alive in the Telling’: Trailblazing Women Lawyers’ Lives, Lived with Law - Kim Rubenstein (Law Text Culture, 2016)
The title of this chapter is inspired by Kirin Narayan’s book - Alive in the Writing: Crafting Ethnography in the Company of Chekhov (2012), who I heard speak at the Australian National University where she was later appointed Professor in the School of Culture, History and Language.1 Kirin engaged us all in her life journey as an anthropologist with verve, passion and energy. Her message was that ‘when words gather together with energy, others places, other people, and other voices stir in parallel life’ (2012: ix). She reminds us that writing can be as powerful as her oral presentation in conveying her drive and spirit and she provides great insights on how we can all seek to be ‘alive in the writing’.